Immunohistochemical retrieval of the principal HIV antigens p24, gp41, and gp120 in formalin fixed tissue: an investigation using HIV infected lymphoblasts and postmortem brain tissue from AIDS cases. Issue 4 (August 1998) - Morrison, H L; Neal, J W; Parkes, A B; Jasani, B
Abstract : This paper describes the use of an autoclaving procedure followed by immunocytochemistry to enhance the detection of the human immunodeficiency virus (HIV) antigens p24, gp41, and gp120. This procedure greatly improved the detection rate of the p24 and gp41 HIV surface antigens in formalin fixed, paraffin wax embedded, HIV positive central nervous system (CNS) tissue while restricting staining to areas of the CNS showing evidence of neuropathology. However, the technique did not improve retrieval of the gp120 antigen in either HIV positive, formalin fixed CNS tissue or HIV infected T lymphoblasts. The inclusion of the high temperature autoclave step was validated using both HIV infected lymphoblasts and pre-adsorption of the specific antibodies with the appropriate recombinant HIV proteins. Using the methodology described here, formalin fixed CNS tissue from potential or known HIV positive cases can be processed reliably and safely. To ensure the reliability of this technique, it is recommended that an assessment of both the p24 and gp41 antigens is undertaken.